Undergraduate nursing students' knowledge, attitudes and self‐efficacy regarding palliative care in China: A descriptive correlational study - Yinghua Zhou; Qiao Li; Wei Zhang (Wiley, 2021)
Abstract Aim To describe nursing students' knowledge, attitudes and self‐efficacy about palliative care and to examine the associations between these variables in China. Design A descriptive correlational study. Methods Undergraduate nursing students (N = 187) at the end of third year of education from a university were surveyed. Measurements included the Chinese versions of the Palliative Care Quiz for Nursing, the Death Attitude Profile‐Revised, the Frommelt Attitude Toward Care of the Dying Scale and the Palliative Care Self‐Efficacy Scale. Descriptive and correlational analyses were performed. Results Although most nursing students had favourable attitudes towards death and caring for the dying, students had low level of knowledge and self‐efficacy regarding palliative care, suggesting the need for integrating palliative care education into nursing curriculum in China. Moreover, special attention should be paid to psychosocial and spiritual care teaching and preparing students to psychologically deal with the challenges in the process of patient's dying.